In vitro release characteristics of matrix tablets: Study of Karaya gum and Guar gum as release modulators - Senapati M.K.; Srinatha A.; Pandit J.K. (My University, 2025)
Matrix tablets of phenylpropanolamine were fabricated using karaya gum and guar gum, alone or in combination with other excipients. The tablets were evaluated for physical characteristics like hardness, weight variation, friability, swelling index and drug content. In vitro release of drug was performed in 0.1N HCl (pH 1.2) for 2 h and the rest of dissolution in phosphate buffer (pH 6.8). The effect of water-soluble (lactose) and water-insoluble (dicalcium phosphate) excipients on drug release was evaluated. All the physical characteristics of the fabricated tablets were within acceptable limits. The tablets with karaya gum exhibited greater swelling indices than those with guar gum. All the batches provided drug release over a period of 6 h. The level of matrix former in the tablets affects drug release. Incorporation of lactose or dicalcium phosphate influenced drug release, but at lower polymer levels only. A combination of karaya gum and guar gum exhibited more sustained release than individual gum.